PELATIHAN PEMANFAATAN VIDEO ANIMASI DALAM PENYULUHAN DAMPAK STUNTING KEPADA PETUGAS BALAI PKB/PLKB KEC.BANG HAJI - Yuza Reswan; Ariksa Abdul Lasin; Leo Tri Anggoro; M Taufik Ma'ruf (JPMTT (Jurnal Pengabdian Masyarakat Teknologi Terbarukan), 2023)
The Family Planning Counseling Center (PKB) / Family Planning Field Officer (PLKB) is located in Kec. Bang Haji, Central Bengkulu Regency, Bengkulu Province. PLKB has difficulties in delivering the extension program that is being held, so that in this street vendor program we provide training on the use of multimedia technology based on video animation for the delivery of the extension program that will be held by officers. And in this training the method we use is to provide training directly to the officers involved in counseling at the PKB/PLKB hall. We hope that this program can make it easier to deliver counseling materials so that it is more easily understood by the people of Kec. bang haji.Â